2021
DOI: 10.2147/oas.s320506
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications and Associated Factors Among Surgical Patients Treated at a Tertiary Hospital, Eastern Ethiopia: A Prospective Cohort Study

Abstract: Background: Surgical intervention is one of the core components of the health care system, yet not free of risks. Once postoperative complications occur, patients are subjected to extra costs for treatment, longer hospital stay, and associated disabilities. The chance of death also increases once patients develop postoperative complications. However, the extent of in-hospital postoperative complications was not well studied in Ethiopia, particularly in the Eastern part of the country. As a result, this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
1
4
2
Order By: Relevance
“…Our study reveals that having surgery for more than two hours does not increase the risk of developing early POCs. Our result is in contrast to that of Bayissa et al's study [ 26 ]. The authors demonstrated that the longer the operative time, the greater the risk of overall complications such as reoperation, medical and surgical complications, and superficial surgical site infections [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study reveals that having surgery for more than two hours does not increase the risk of developing early POCs. Our result is in contrast to that of Bayissa et al's study [ 26 ]. The authors demonstrated that the longer the operative time, the greater the risk of overall complications such as reoperation, medical and surgical complications, and superficial surgical site infections [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our result is in contrast to that of Bayissa et al's study [ 26 ]. The authors demonstrated that the longer the operative time, the greater the risk of overall complications such as reoperation, medical and surgical complications, and superficial surgical site infections [ 26 ]. These discrepancies may be related to the teaching hospital and most surgeries performed by residents with attending supervision, leading to more time for performing surgical procedures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…40 Post-operative complication: Adverse events such as pneumonia, meningitis, wound infection, postoperative wound dehiscence, reoperation occur as a consequence of tissue injury due to surgery or anesthesia, following Surgery and Anesthesia. 41 Unfavorable outcome: is the mortality/death following TBI.…”
Section: Operational Definitionmentioning
confidence: 99%
“…Studies reported adverse events can occur in up to 14% of patients who have undergone surgery while mortality ranges between 1% and 4% 2 3. Similarly in Ethiopia, adverse events occur in 12% of surgical patients 4. However, the incidence of surgical complications has not shown a significant change over the past two decades 5 6.…”
Section: Introductionmentioning
confidence: 99%